1958
DOI: 10.1111/j.1365-2621.1958.tb17534.x
|View full text |Cite
|
Sign up to set email alerts
|

ENZYME ACTION AND OFF‐FLAVOR IN FROZEN PEASa

Abstract: Enzymes are believed to be responsible for the development of off-flavor in raw and underblanched vegetables during frozen storage (1). A variety of enzymes have been suggested as being causative agents in flavor deterioration (l), but interest has centered mainly around catalase and peroxidase. Tests for the presence of these two enzymes have long been used as criteria of adequacy of blanching of vegetables prior to freezing. Furthermore, a reasonably good correlation has been observed between the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1958
1958
1996
1996

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…LIP has been implicated in loss of chlorophyll and production of off-flavors in frozen green peas (Wagenknecht and Lee, 1958). However, results have not been presented detailing the activity of the enzyme under varying blanch conditions and subsequent frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…LIP has been implicated in loss of chlorophyll and production of off-flavors in frozen green peas (Wagenknecht and Lee, 1958). However, results have not been presented detailing the activity of the enzyme under varying blanch conditions and subsequent frozen storage.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies have shown that POD is not directly involved in quality deterioration of frozen unblanched vegetables and its complete inactivation may result in overblanching (Williams et al, 1986). The measure of LOX activity has been suggested as an indicator of adequacy of blanching for several vegetables (Axelrod et al, 1981;Sheu and Chen, 1991;Chen and Hwang, 1988;Williams et al, 1986;Chen and Whitaker, 1986;Wagenknecht and Lee, 1958) including sweet corn (Garrote et al, 1985;Wagenknecht, 1959). It is closely related to destruction of essential fatty acids, off-flavor development and pigment degradation.…”
Section: Introductionmentioning
confidence: 99%
“…IT HAS BEEN well documented that holding plant tissue at -'2O"C retards but does not totally prevent quality changes and that these changes are associated with enzymatic action (Joslyn, 1949;Lee et al, 1955;Wagenknecht and Lee, 1958;Pinsent, 1962). Several factors affect the rate of enzyme inactivation during heating (Aylward and Haisman, 1969).…”
Section: Introductionmentioning
confidence: 99%